2018
DOI: 10.1111/jfr3.12492
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of SAC‐SMA and Adaptive Neuro‐fuzzy Inference System for real‐time flood forecasting in small urban catchments

Abstract: Growing urbanisation and imperviousness have augmented magnitudes of peak flows, resulting in flooding especially during extreme events. Flood forecast of extreme events can rely on real‐time ensemble flood forecasting systems. Such systems often use predictions from physical models and precipitation ensembles to predict downstream urban flood hydrographs. However, these methods are seldom used in small catchments, where flood predictions may assist emergency management. We explore the relative utility of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This study divides rainfall into two categories according to method of observation: (1) traditionally observed rainfall, i.e., ground stations (hydrological stations, rainfall stations; 41 studies use ground-based observed rainfall as the model input); (2) new technology for rain measurement, i.e., rainfall data obtained via emerging technologies such as remote sensing, radar, numerical weather forecasting, and Web crawling (seven articles employed this method). Urban flood modeling has been an area of great research interest in recent years (Figure (3). The present study represents a systematic review of comprehensive observation of rainfall methods and research trends.…”
Section: Study Search and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study divides rainfall into two categories according to method of observation: (1) traditionally observed rainfall, i.e., ground stations (hydrological stations, rainfall stations; 41 studies use ground-based observed rainfall as the model input); (2) new technology for rain measurement, i.e., rainfall data obtained via emerging technologies such as remote sensing, radar, numerical weather forecasting, and Web crawling (seven articles employed this method). Urban flood modeling has been an area of great research interest in recent years (Figure (3). The present study represents a systematic review of comprehensive observation of rainfall methods and research trends.…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…Climate change and the urban rain island effect have exacerbated the problem via increasing occurrence of extreme rainfall events [2]. Continuous development and expansion of cities have led to the transformation of natural permeable surfaces into impervious underlay surfaces, which accelerate the formation of runoff [3]. At the same time, continuous economic development has led to more severe flood losses [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being a spatially aggregated model, it normally presents better results compared to other hydrological models and is often used as a benchmark for testing new models (Wijayarathne & Coulibaly 2020, Birhanu et al 2018. SAC-SMA model has been widely used worldwide in different research areas including flood forecasting (Demargne et al 2014, Roodsari et al 2019, streamflow prediction in ungauged basins (Kratzert et al 2019), parameters transferability using soil moisture characteristics (Wang et al 2023), applications of long short-term memory (LSTM) networks in hydrology modeling (Kratzert et al 2018).…”
Section: Introductionmentioning
confidence: 99%